What Can We Learn About the Decline in U.S. Union Membership from International Data? - Solomon W. Polachek (Institute for the Study of Labor (IZA), 2003)
This paper is composed of two parts. First, using international data, I corroborate that union density in the U.S. declined because of asymmetric growth between the union and nonunion sectors. I show union density to increase in countries experiencing strong manufacturing growth, and to decline in countries undergoing large women?s increases in nonagricultural employment. Second, I borrow from international relations research on war and peace to develop a cogent reason why union density differs by sector. In this vein, I apply a model primarily used to describe bilateral political interactions to figure out why workers often engage in hostile activities such as strikes. In doing so, I look at the contentious rather than the cooperative ?face? of unions.
Keywords: J4; F16; J5; 330; unions; union density; manufacturing growth; international relations; Gewerkschaftlicher Organisationsgrad; Drei-Sektoren-Hypothese; Strukturwandel; Branchenentwicklung; Schätzung; Vereinigte Staaten; Welt